Elimination of Butylcycloheptylprodigiosin as a Known Natural Product Inspired by an Evolutionary Hypothesis for Cyclic Prodigiosin Biosynthesis - Jones, Brian T.; Hu, Dennis X.; Savoie, Brett M.; Thomson, Regan J. (Journal of natural products (Washington, D.C.), 2013)
The cyclic prodigiosins are an important family of bioactive natural products that continue to be the subject of numerous structural, synthetic, and biosynthetic studies. In particular, the structural assignments of the isomeric cyclic prodigiosins butylcycloheptylprodigiosin (BCHP) and streptorubin B have been the cause of significant confusion. Herein, we report detailed studies regarding the electron impact (El) mass spectra of synthetic BCHP and streptorubin B that have allowed us to distinguish the two compounds in the absence of quality historical isolation NMR data. On the basis of these fragmentation differences, the status of BCHP as a natural product is challenged. The proposed mechanism of fragmentation is supported by the El mass spectra of synthetic pentyl-chain analogues of BCHP and streptorubin B, X-ray crystallography, and DFT calculations. Elimination of BCHP from the prodigiosin family supports a proposed evolutionary hypothesis for the surprising biosynthesis of cyclic prodigiosins.